Association between dietary niacin intake and mortality among US individuals with chronic obstructive pulmonary disease: data from the national health and nutrition examination survey 1999–2018 - Fu, Chengfeng; Zhang, Lixia; Luo, Jing; Zhang, Yingying (Frontiers in Nutrition, 2025)
Background and aimsChronic obstructive pulmonary disease (COPD) is a long-lasting condition that significantly hinders respiratory function. Niacin, a crucial nutrient in the diet, is essential for maintaining general health. However, research on the effects of niacin on the mortality risk among individuals with COPD is sparse. Hence, this study aims to investigate the relationship between dietary niacin intake and mortality within this specific cohort of individuals.Methods and resultsA total of 3,674 self-reported COPD individuals from the National Health and Nutrition Examination Survey (NHANES) 1999–2018 were included in this study. The Cox proportional hazards model assessed the association between niacin intake and all-cause/cardiovascular disease (CVD) mortality. Kaplan–Meier curves illustrated survival based on niacin intake. Subgroup and sensitivity analyses were conducted to assess the robustness of the results. During an average follow-up period of 8.3 years, 1,085 all-cause deaths occurred, including 323 CVD-related deaths. A 10 mg/day niacin increase was associated with a 12% lower all-cause and 13% lower CVD mortality risk. Compared to the low dietary niacin intake group, the high intake group had a hazard ratio (HR) of 0.67 (95% CI: 0.56–0.82, p < 0.001) for all-cause mortality and 0.53 (95% CI: 0.37–0.77, p = 0.001) for CVD mortality. Kaplan–Meier survival curves indicated higher survival rates in the high-niacin group.ConclusionA higher dietary intake of niacin was associated with lower all-cause and CVD mortality among individuals with COPD.